Oncology Nurses' Perceptions of Participation in Clinical Trials Among Patients With Developmental Disabilities. - Becker, Heather; Phillips, Carolyn; Haack, Irina; Mikan, Sabrina Q. (Journal of Oncology Navigation & Survivorship, 2025)
Background: Participation in clinical trials among people with disabilities, particularly developmental disabilities (DD), has been limited. Nurses, particularly those providing navigation, can play a key role in educating patients about clinical research. Objective: To explore oncology nurses' reports of the inclusion of individuals with DD in clinical trials. Methods: We surveyed the oncology nurses working in a large statewide outpatient provider network that conducts clinical trials about care for their adult patients with DD. The online survey included questions about their professional background and care of patients with DD, as well as items about referral and participation of patients in clinical trials. Results: Nurses in this sample worked as oncology nurses for 12 years on average, and 65% had provided care for between 1 and 6 patients with DD. Seven respondents had not cared for any of these patients. Among the 69 nurses who responded regarding clinical trial referrals, only 16 indicated that, to their knowledge, eligible patients with DD were referred for clinical trials; 7 were aware of patients with DD who did participate. Conclusions: Concerns about patients' ability to voluntarily consent to participate in research must be balanced against the ethical principle of the right of individuals with disabilities to participate fully in healthcare research. This study's results suggest that much work remains to be done to make clinical trials accessible to cancer patients with DD. Nurses, along with other healthcare professionals, must understand how to educate, recruit, and retain patients with DD in clinical research. This includes fostering informed consent for potentially vulnerable groups and overcoming other barriers to clinical trial participation.